In Vitro and In Vivo Differences in Murine Third Complement Component (C3) Opsonization and Macrophage/Leukocyte Responses to Antibody-Functionalized Iron Oxide Nanoworms - Wang, Guankui; Griffin, James I.; Inturi, Swetha; Brenneman, Barbara; Banda, Nirmal K.; Holers, V. Michael; Moghimi, Seyed Moein; Simberg, Dmitri (Frontiers in Immunology, 2017)
Balancing surface functionalization and low immune recognition of nanomedicines is a major challenge. Opsonization with the third component of the complement protein (C3) plays a major role in immune cell recognition of nanomedicines. We used dextran-coated superparamagnetic iron oxide nanoworms (SPIO NWs) to study the effect of surface functionalization on C3 opsonization in mouse serum and subsequent macrophage/leukocyte recognition in vitro as well as on intravenous injection into mice. Previously, we found that in mouse serum, SPIO NWs became opsonized with C3 via complement lectin pathway. Crosslinking the dextran shell with epichlorohydrin significantly decreased C3 opsonization and uptake by mouse peritoneal macrophages. Crosslinked nanoworms (NWs) further functionalized with polyethylene glycol (PEG) or with PEG-antibody (Ab) (~160 IgG molecules/particle) did not show an increase in C3 opsonization and peritoneal macrophage uptake in vitro. Following tail vein injection into mice, plain crosslinked NWs and PEGylated crosslinked NWs showed very low C3 opsonization and mouse leukocyte uptake. However, Ab-decorated crosslinked NWs showed significant C3 opsonization and high level of complement-dependent uptake by leukocytes in mice. Decreasing the number of conjugated Abs to 46 IgG molecules/particle significantly reduced C3 opsonization and leukocyte uptake. Using fresh mouse lepirudin plasma rather than serum showed better correlation with C3 opsonization in vivo. The reason for this difference could be related to the known instability of complement classical pathway in mouse sera. Our data illustrate that fine-tuning in nanoparticle surface functionalization with Abs is required to avoid excessive complement activation and complement-mediated immune uptake in mice, and raise issues with in vitro immunological assays of nanomedicines intended to mimic in vivo conditions.